AUTOMATION IMPROVEMENT FOR GIS-BASED APPLICATIONS DEPLOYMENT IN FAST GROWING HIGH SCALABILITY DATA-ROOMS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper presents the viability and importance of automation in deploying and managing software systems to reduce costs. Automation allows for optimizing time spent on resource deployment and configuration and simplifying the upgrade process. A real-world geographic information system (GIS) project illustrates these improvements by automating WGS84 & STEREO70 conversion modules for software systems.
Keywords: Automation; Software deployment; Geographic information system (GIS) conversion; Software resources configuration